The Effect of Clinical Supervision by Ophthalmologists on the Severity of Diabetic Retinopathy in Kapuas District - Rosmaryati Manalu; Syamsul Arifin; Dewi Indah Noviana Pratiwi; Muhammad Ali Faisal; Rosihan Adhani; Lenie Marlinae; Herawati; Muhammad Bayu Sasongko (Jurnal Kesehatan Masyarakat, 2026)
Diabetic retinopathy (DR) is a microvascular complication of diabetes mellitus (DM) and a leading cause of blindness among productive-age adults. Globally, the prevalence of DR reaches 34.6%, while in Indonesia it is 43.1%, making it the second most common diabetes complication after nephropathy. In Kapuas District, the 2022 data reported 5,390 DM patients and 56 DR cases, with a growing trend each year, particularly in areas with limited health services. This study, conducted in 2025, aimed to analyze the effect of clinical supervision by ophthalmologists on DR severity in relation to treatment duration, age, and healthcare access distance. A quasi-experimental design with a pre-test and post-test approach was applied to 52 non-proliferative DR patients divided into intervention (clinical supervision) and control groups. Results showed that clinical supervision effectively maintained mild DR conditions (p=1.000), while the non-supervised group exhibited increased severity (p=0.025). Longer treatment duration correlated with stable DR (p=0.000), age influenced severe DR (p=0.033), and healthcare distance affected moderate DR (p=0.045). Clinical supervision by ophthalmologists effectively slows DR progression, particularly among productive-age patients and those with limited access to eye care services.